Hypertension Treatment Intensification Among Stroke Survivors With Uncontrolled Blood Pressure. Issue 2 (February 2015) - Roumie, Christianne L.; Zillich, Alan J.; Bravata, Dawn M.; Jaynes, Heather A.; Myers, Laura J.; Yoder, Joseph; Cheng, Eric M.
<x xml:space="preserve">Abstract</x> Background and Purpose— We examined blood pressure 1 year after stroke discharge and its association with treatment intensification. Methods— We examined the systolic blood pressure (SBP) stratified by discharge SBP (⩽140, 141–160, or >160 mm Hg) among a national cohort of Veterans discharged after acute ischemic stroke. Hypertension treatment opportunities were defined as outpatient SBP >160 mm Hg or repeated SBPs >140 mm Hg. Treatment intensification was defined as the proportion of treatment opportunities with antihypertensive changes (range, 0%–100%, where 100% indicates that each elevated SBP always resulted in medication change). Results— Among 3153 patients with ischemic stroke, 38% had ≥1 elevated outpatient SBP eligible for treatment intensification in the 1 year after stroke. Thirty percent of patients had a discharge SBP ⩽140 mm Hg, and an average 1.93 treatment opportunities and treatment intensification occurred in 58% of eligible visits. Forty-seven percent of patients discharged with SBP 141 to160 mm Hg had an average of 2.1 opportunities for intensification and treatment intensification occurred in 60% of visits. Sixty-three percent of the patients discharged with an SBP >160 mm Hg had an average of 2.4 intensification opportunities, and treatment intensification occurred in 65% of visits. Conclusions— Patients with discharge SBP >160 mm Hg had numerous opportunities to improve hypertension control. Secondary stroke prevention efforts should focus on initiation and review of antihypertensives before acute stroke discharge; management of antihypertensives and titration; and patient medication adherence counseling.